Sobre el ángulo de escritura en la documentación de San Isidoro de León: evolución de los siglos XI al XIII - Martín López, María Encarnación (Estudios humanísticos. Geografía, historia y arte, 2021)
The technical elements of writing have proved to be essential when establishing a serious and definitive assessment of documentary form - specifically jis external characteristics - and tradition. One of these technical elements is the angle of writing. This paper is meant as a first approach to the issue, which, it is our opinion, places the angle of writing, as well as its assessment, in the foreground of documentary criticism considered as tradition.